Structural and luminescence properties of magnesium boro-tellurite doped europium and dysprosium ion ceramic - Bohari, Nur Zu Ira (2015)
A series of xTeO2-(70-x)B2O3-30MgO samples with 0 = x = 70 mol% and doped samples with composition of 100-y(30TeO2-40B2O3-30MgO)-yEu3+, 100- z(30TeO2-40B2O3-30MgO)-zDy3+, and 100-y-z(30TeO2-40B2O3-30MgO)-yEu3+- zDy3+ with 0.2 = y = 2 mol% and 0.2 = z = 2 mol% were prepared via solid-state reaction method. All the samples were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy, Raman spectroscopy, energy dispersive Xray spectroscopy (EDX), field emission scanning electron microscopy (FESEM) and photoluminescence spectroscopy. The XRD results of the samples prepared at 650oC to 850oC showed that the major phase was Mg(Te2O5) while MgTe6O13, Mg2(B2O5) and MgB4O7 were observed as a minor phase. The phases of Dy(BO2)3, Dy2Te4O11, EuB2O4 and Eu2Te4O11 were observed in the XRD patterns of doped samples. The EDX analyses confirmed the presence of boron (B), magnesium (Mg), tellurium (Te), oxygen (O), europium (Eu) and dysprosium (Dy) elements. In addition, the weight percentage of boron (B) decreases with the increase of x mol%. Based on the FESEM images, the xTeO2-(70-x)B2O3-30MgO samples with 0 = x = 70 mol% prepared at 750oC consist basically of sub-micron size agglomerates of irregular shape. The surface morphology of Eu3+, Dy3+ and Eu3+-Dy3+ doped samples is more agglomerated compared to the 30TeO2-40B2O3-30MgO samples. The grain sizes of samples doped with Eu3+ (1.91 µm), Dy3+ (1.87 µm) and Eu3+-Dy3+ (2.84 µm) are smaller than the grain size of the undoped sample (2.99 µm). There were six main regions observed in IR spectra which are due to the B-O-B (400-590 cm-1), Te-O-Te (550 and 610 cm-1), TeO2 (600-800 cm-1), TeO3 (757 cm-1), BO4 (840-1200 cm-1) and BO3 (1300-1400 cm-1) vibrations. The observed spectra also show greater bands for tellurite network with the increase of x mol%. From the Raman spectra, the intensity of the peaks due to Te-O-Te, TeO2 and TeO3 groups increases with the increase of x from 0 to 30 mol%. The luminescence spectra of 100-y(30TeO2-40B2O3-30MgO)- yEu3+ with 0.2 = y = 2 mol% showed that there was an increase in the emission intensity which results in the enhancement of the red emission from the samples. All the spectra of 100-z(30TeO2-40B2O3-30MgO)-zDy3+ samples with 0.2 = z = 2 mol% show the main characteristic emission lines of Dy3+, which consist of magnetic dipole transition, 4F9/2?6H15/2 at 484.19 nm (blue), and hypersensitive electric dipole transition, 4F9/2?6H13/2 at 578.44 nm (yellow). The observed emission spectra of 100-y-z(30TeO2-40B2O3-30MgO)-yEu3+-zDy3+ samples with 0.2 = y = 2 mol% and 0.2 = z = 2 mol% exhibit three strong bands centered at 483.78 nm, 578.97 nm and 616.83 nm which correspond to the 4F9/2-6H15/2 (Dy3+), 4F9/2-6H13/2 (Dy3+) and 5D0?7F2 (Eu3+) transition respectively. The yellow emission (4F9/2-6H13/2) becomes a dominant peak in the emission spectra compared to the other emissions. The longest decay time was observed from the transition in europium and dysprosium ions.